Advances in Virus Biorecognition and Detection Techniques for the Surveillance and Prevention of Infectious Diseases - Shuwen Luo; Lihong Yin; Xiaohui Liu; Xuemei Wang (Biosensors)
Viral infectious diseases pose a serious threat to global public health due to their high transmissibility, rapid mutation rates, and limited treatment options. Recent outbreaks of diseases such as plague, monkeypox, avian influenza, and coronavirus disease 2019 (COVID-19) have underscored the urgent need for efficient diagnostic and surveillance technologies. Focusing on viral infectious diseases that seriously threaten human health, this review summarizes and analyzes detection techniques from the perspective of combining viral surveillance and prevention advice, and discusses applications in improving diagnostic sensitivity and specificity. One of the major innovations of this review is the systematic integration of advanced biorecognition and detection technologies, such as bionanosensors, rapid detection test strips, and microfluidic platforms, along with the exploration of artificial intelligence in virus detection. These technologies address the limitations of traditional methods and enable the real-time monitoring and early warning of viral outbreaks. By analyzing the application of these technologies in the detection of pathogens, new insights are provided for the development of next-generation diagnostic tools to address emerging and re-emerging viral threats. In addition, we analyze the current progress of developed vaccines, combining virus surveillance with vaccine research to provide new ideas for future viral disease prevention and control and vaccine development, and call for global attention and the development of new disease prevention and detection technologies.